Peran Komitmen Organisasi terhadap Kesejahteraan Karyawan Perguruan Tinggi Islam di Bandung - Wangi, Eneng Nurlaili; Fahmi, Irfan; Lutfiani, Siti Mutya (Psympathic : Jurnal Ilmiah Psikologi, 2022)
This studi aims to examine the effect of organizational commitment on employees' well-being. This causality research involvig 721 respondents recruited using simple random sampling. Organizational commitment was measured using Organizational Commitment Questionnaire (OCQ) based on the concept from Meyer and Allen, while well-being was measured using instrument developed by Butler and Kern. The results show that affective and normative organizational commitment did not affected well-being, while continuance organizational commitment has a significant effect on well-being. Employees with affective-based organizational commitment show different behavior compared to continuance- and normative-based. This commitment made the employees choose to continue the job by considering how comfortable they work, which is related to their well-being.